The main trends in the development of public-private partnership in Kazakhstan on the basis of social-entrepreneurial corporations - Magda, R.; Kuttybai, M.; Davletbaeva, N.; Kasymova, N. (BUKETOV BUSINESS REVIEW, 2019)
In the article the potential opportunities of the development of mechanisms for public-private partnership in Kazakhstan on the basis of specialized institutional organizations as social-entrepreneurial corporations are discussed. In the context of Kazakhstan, the issues of development of public-private partnership are solved through the creation and operation of social-entrepreneurial corporations in each region. Socialentrepreneurial corporations as regional development institutions are created in the form of a holding company, and their main activity is aimed at attracting investment resources to the region for the implementation of infrastructure and innovative projects, promotion of the development of business initiatives of small and medium-sized businesses. The analysis of the main indicators of the functioning of a separate socioentrepreneurial corporation has been carried out, the systemic problems have been identified that impede their full development, and also the priority directions for their further development have been established. Currently, on the basis of regional SECS, the necessary elements are being created for the formation of a modern model of continuous investment process using the mechanisms of public-private partnership.